PENGARUH ASIMETRI INFORMASI DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Ayu Apriliani Hidayat; Ahmad Juanda; Ahmad Wajuya Jati (Universitas Muhammadiyah Malang, 2019)
This study aims to examine the relation of information asymmetry and leverage to earnings management in mining companies listed at Indonesian Stock Exchange. Earnings management as the dependent variabel is measured by discretionary accruals. The populations of this study were all mining companies that listed at Indonesian Stock Exchange period 2016-2018. The sample used in this research is about 24 companies through purposive sampling method. The methode of analysis used in this study is panel data regression. The results showed that the information asymmetry hasn’t been approved for having significant and negative relation on earnings management. However, leverage have significant and positive relation on earnings management.